2008
DOI: 10.1007/s00167-008-0633-8
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic reconstruction of chronic AC joint dislocations by transposition of the coracoacromial ligament augmented by the Tight Rope device: a technical note

Abstract: We present a new arthroscopic technique for chronic AC joint dislocations with coracoacromial ligament transposition and augmentation by the Tight Rope device (Arthrex, Naples, USA). First the glenohumeral joint is visualised to repair concomitant lesions, such as SLAP lesions, if needed. Once the rotator interval is opened and the coracoid is identified, the arthroscope is moved to an additional anterolateral portal. A 1.5 cm incision is made 2 cm medial to the AC joint. After drilling a 4 mm hole with a cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 11 publications
0
31
0
4
Order By: Relevance
“…[18][19][20] Reconstruction using 2 adjustableeloop-length suspensory fixation devices showed greater vertical strength and horizontal strength compared with the native ligament in a cadaveric biomechanical study. Hosseini et al 21 suggested that simultaneous use of both the coracoacromial ligament transfer and the CC fixation technique using the single adjustableeloop-length suspensory fixation device can be effective for the treatment of AC joint dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Reconstruction using 2 adjustableeloop-length suspensory fixation devices showed greater vertical strength and horizontal strength compared with the native ligament in a cadaveric biomechanical study. Hosseini et al 21 suggested that simultaneous use of both the coracoacromial ligament transfer and the CC fixation technique using the single adjustableeloop-length suspensory fixation device can be effective for the treatment of AC joint dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…33,34) However, the first generation of this device consisted of a smaller round proximal button that had the potential to erode the clavicle and led to loss of reduction. 35,36) Since a larger proximal button was developed, no erosion or failure has occurred using this surgery. The titanium buttons, which are positioned centrally on top of the clavicle and under the coracoid, are connected with a continuous loop of No.…”
Section: Discussionmentioning
confidence: 99%
“…Verschiedene weitere Techniken wurden beschrieben, zum einen, um die mechanischen Eigenschaften des CC-Bandes bei dessen Transfer zu verbessern, zum anderen, um nur einen Teil des Bandes zu transferieren [24,44]. So kombinierten Hosseini et al [19] den Transfer mit einem TightRope™, um eine bessere und sicherere Stabilisierung zu erhalten. Auch Lafosse et al [24] und Boileau et al [1] führen diese modifizierte Weaver-Dunn-Technik arthroskopisch durch und vermeiden damit Komplikationen der offenen Operationstechnik.…”
Section: Nichtanatomische Rekonstruktionunclassified